A Comparative Carbon Footprint Analysis of Disposable and Reusable Vaginal Specula. Issue 6 (June 2020) - Donahue, Laura M.; Hilton, Stephen; Bell, Sarah G.; Williams, Brent C.; Keoleian, Gregory A.
Abstract : (Abstracted from Am J Obstet Gynecol 2020; doi: 10.1016/j.ajog.2020.02.007) In an attempt to save time, as well as reduce costs and transmission of infections, many health care systems in the United States have increased use of disposable medical equipment, which generally decrease costs upfront compared with their reusable alternatives. Use of disposable instruments, however, is associated with increased solid waste production and may increase greenhouse gas emissions, negatively impacting the environment.